Beamforming Algorithm Based on the Orthogonal Phase Bases with Trigonometric Estimation for Microwave Power Transfer Systems - Koo, Hyungmo; Shin, Jaekyung; Choi, Woojin; Bin, Soohyun; Oh, Hansik; Lim, Hongjun; Lee, Kang-Yoon; Hwang, Keum cheol; Yang, Youngoo (IEEE access, 2022)
Microwave power transfer (MPT) has been widely studied, as sensors or mobile/wearable devices have been used, especially for IoT applications. A beamforming algorithm is essential and important for both the performance and the system complexity of MPT systems. In this paper, a beamforming algorithm that requires only 3 N -2 transmission sequences for the Tx array with N elements to estimate the optimum set of the transmission phases is proposed. The proposed algorithm is simply based on trigonometric calculations, and can be directly applied to an MPT system without element calibration. Calculation of the optimum phase set of the Tx only requires the information of the received power level from the Rx. Since simultaneous phase shifting of the multiple elements is performed during the power transmission sequence, it can have a relatively high Rx SNR, compared to the methods based on phase shifting of only one element at each sequence. In addition, optimum transmission phase sets for multiple Rx's can be obtained from a beamforming procedure using the proposed algorithm, if the received power levels from the multiple Rx's are collected. For verification of the proposed algorithm, a 5.2 GHz 8×4 Tx array having an output power of 0.5 W per Tx element was implemented. Beamforming experiment was performed using the proposed algorithm. A received power of 45 mW at 2 m distance was achieved, which is very close to the simulated value.